Efficacy of pre - operative axillary ultrasonography in excluding nodal disease – can it replace sentinel lymph node biopsy in early stage breast cancer? - Javed, Nida; Sidra Afzal; Iqbal, Ejaz; Aleem, Javaria; Parvaiz, Muhammad Asad; Abu Bakar, Muhammad (Journal of the Pakistan Medical Association, 2023)
Objectives: To determine false negative rate, negative predictive value and the factors predicting false negativity of pre-treatment axillary ultrasound. Method: The retrospective study was conducted at Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan, and comprised data from January 2019 to December 2020 of patients with normal lymph nodes on ultrasound, tumour stages T1, T2 or T3 having invasive cancer who underwent sentinel lymph node biopsy. Ultrasound findings were compared with the biopsy results, dividing the sample into false negative group A and true negative group B. Clinical, radiological, histopathological parameters and therapeutic strategies were compared between the two groups. Data was analysed using SPSS 20. Results: Of the 781 patients with mean age 49.39±11.51 years, 154(19.7%) were in group A and 627(80.2%) were in group B, with negative predictive value of 80.2%. Initial tumour size, histopathology, tumour grade, receptors, timing of chemotherapy, and type of surgery has significant difference between the groups (p<0.05). Multivariate analysis showed larger, high-grade, progesterone receptor negative and human epidermal growth factor receptor 2 positive tumours were significantly associated with lower false negative rate on axillary ultrasound (p<0.05). Conclusion: Axillary ultrasound was found to be effective in ruling out axillary nodal disease, especially in patients with high-burden axillary disease, aggressive tumour biology, larger tumour size and higher timour grade. Key Words: Axillary ultrasound, Sentinel lymph node biopsy, Early breast cancer, False negativity.